Different dietary electrolyte balance values on performance, egg, and bone quality of Japanese quail (Coturnix Coturnix Japonica) under heat stress - Cruvinel, Jessica Moraes [UNESP]; Urayama, Priscila Michelin Groff [UNESP]; dos Santos, Tatiane Souza [UNESP]; Denadai, Juliana Célia [UNESP]; Muro, Everton Moreno [UNESP]; Dornelas, Livia Carrasco [UNESP]; Pasquali, Guilherme Aguiar Mateus [UNESP]; Neto, Armando Carlos Contin [UNESP]; Zanetti, Leonardo Henrique [UNESP]; Netto, Raiumundo Gonçalves Ferreira [UNESP]; Sartori, José Roberto [UNESP]; Pezzato, Antonio Celso [UNESP] (Springer Nature, 2021)
The objective of this study was to evaluate the productive performance and quality of eggs and bones of Japanese quails that received different dietary electrolyte balance (EB) and were submitted to thermoneutrality or heat stress conditions. Eight hundred Japanese quails of 21 days of age were selected and distributed randomly in two bioclimatic chambers: thermoneutral chamber (23 °C ± 2 °C) and heat-stress chamber (33 °C ± 2 °C). The treatments were in a 2 × 5 factorial arrangement, with two temperatures and five EB levels (165, 215, 265, 315, 365 mEq/kg) with four replicates of 20 birds each. The productive performance and egg quality (in 3 cycles of 21 days) were measured. At 105 days old, the bone quality was evaluated. Data were analyzed by Minitab, and the means were compared by Tukey’s test and regression test for levels (P < 0.05). Quails submitted to thermoneutrality showed better performance and egg and bone quality. The highest production rate was the EB level of 265 mEq/kg. Low values of EB (165 and 215 mEq/kg) and high values (365) impaired egg quality, and the ideal was 315 mEq/kg. Lower levels of balance provided poor bone density. In conclusion, the results of this study indicated that heat stress impairs the production and quality of quail eggs and bones. Furthermore, by using intermediate EB levels (265 and 315) mEq/kg, it is possible to improve egg production and egg quality, and using high levels increases bone mineral density.
Keywords: Acid-base homeostasis; Bioclimatology; Bone quality; Quail eggs; Quail nutrition